Assessing Phytophthora cinnamomi seasonal root colonisation patterns and pathogen response to management practices (phosphonates and rootstock tolerance) in South African avocado orchards - Jolliffe, Jenna Bryanne (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.